2022
DOI: 10.1007/s00420-022-01851-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk communication about work-related stress disorders in healthcare workers: a scoping review

Abstract: Purposes Healthcare workers are at risk of stress-related disorders. Risk communication can be an effective preventive health measure for some health risks, but is not yet common in the prevention of stress-related disorders in an occupational healthcare setting. The overall aim is to examine whether risk communication was part of interventions aimed at the prevention of stress-related disorders in healthcare workers. Method We performed a scoping review u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…Preventing PD among HCWs is of utmost importance, given the far‐reaching adverse effects it can have on their health, the organization, and society as a whole 1,4 . While preventive interventions often rely on questionnaires to detect HCWs at risk, the incorporation of objective measurements in the assessment of PD holds promise, overcoming some of the limitations associated with questionnaires 6 . In line with the objective of this study, we identified 14 out of 24 candidate PD biomarkers in the SC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preventing PD among HCWs is of utmost importance, given the far‐reaching adverse effects it can have on their health, the organization, and society as a whole 1,4 . While preventive interventions often rely on questionnaires to detect HCWs at risk, the incorporation of objective measurements in the assessment of PD holds promise, overcoming some of the limitations associated with questionnaires 6 . In line with the objective of this study, we identified 14 out of 24 candidate PD biomarkers in the SC.…”
Section: Discussionmentioning
confidence: 99%
“…Oftentimes, questionnaires are utilized for the assessment of PD. However, commonly used questionnaires that screen for PD do not appear to have adequate measurement properties and diagnostic accuracy 6 . This limitation of questionnaires negatively influences the diagnostic accuracy, leading to over‐estimation or under‐estimation of PD in HCW 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, HCWs have been classified as one of the occupational populations that are more vulnerable to stress-related disorders (Emal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for individuals with already stressful occupations, rotating shift schedules may increase stress and the risk of developing mental health disorders (Brown et al, 2020). Consequently, HCWs have been classified as one of the occupational populations that are more vulnerable to stress-related disorders (Emal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%